2017
DOI: 10.1136/bmjopen-2017-015915
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric validation of the Coronary Revascularisation Outcome Questionnaire (CROQv2) in the context of the NHS Coronary Revascularisation PROMs Pilot

Abstract: ObjectivesThe Coronary Revascularisation Outcome Questionnaire (CROQ) is a patient-reported outcome measure (PROM) for coronary artery bypass surgery (CABG) and percutaneous coronary intervention (PCI). We tested the psychometric properties of a modified version (CROQv2) when administered in a National Health Service (NHS)/Department of Health (DH) funded pilot of PROMs for coronary revascularisation.DesignPsychometric validation study.Setting11 English hospitals in the UK taking part in the NHS/DH funded pilo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…Earlier studies have shown that patients with known heart disease tend to report lower HRQOL than patients without previous known disease. 13 In this study the patients with known heart disease scored significantly lower on four of the six CROQ scales. The CROQ’s satisfaction scale which includes questions about rehabilitation, treatment results and how the patients’ consider their heart disease now compared with before the PCI showed a significant difference between the groups.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Earlier studies have shown that patients with known heart disease tend to report lower HRQOL than patients without previous known disease. 13 In this study the patients with known heart disease scored significantly lower on four of the six CROQ scales. The CROQ’s satisfaction scale which includes questions about rehabilitation, treatment results and how the patients’ consider their heart disease now compared with before the PCI showed a significant difference between the groups.…”
Section: Discussionmentioning
confidence: 52%
“…The initial version of the CROQ was published in 2004, 4 but it has been revised and revalidated recently. 13 In recent years, the techniques of PCI treatment have evolved and the instrument has been modified to reflect these changes (CROQv2). Nowadays PCI is more often done via the radial artery than the femoral artery.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This will collaborate with patients, carers, research groups and other relevant stakeholders through various methodologies including systematic reviews, expert consensus statements and Delphi processes in order to develop and harmonise outcome reporting . An example of what can be achieved was recently demonstrated in the NHS Coronary Revascularisation PROMs pilot study . The authors modified a pre‐existing, validated questionnaire (the Coronary Revascularisation Outcomes Questionnaire), which is used to measure outcomes before and after coronary revascularisation and undertook a psychometric validation study across 11 hospitals in England.…”
Section: Proms Prems or Both?mentioning
confidence: 99%